Divulgação científica : percepções sobre meio ambiente na revista Ciência Hoje. - Brandão, Alessandra Gomes (2007)
The present work has as analysis object the subjects on environment published in the magazine Ciência Hoje, in the period of January of 2003 the December of 2006, with the objective of investigating how the scientific community presents the ambient questions for the Brazilian society, by a periodic.The analysis of the divulgation of the contents about the environment was carried through, identificating if both the chains of thoughts in defense of the nature ( biocentric and anthropocentric) appear in publications; as the terms Environment and Nature appear in the texts, and still as the concept of sustainable development is presented by the authors of publications. It was also the objective of this work the editorial analysis of all editions of the period. We identify that the scientific divulgation of the environment subjects in Ciência Hoje keeps a biologized characteristic of the environment crisis, not presenting important reflections concerning the social relations that are the focus of the question, leading to the knowledge of the public a disciplined and dispolitized vision of the environment.